PENGARUH PENGUMUMAN PEMBAYARAN DIVIDEN TUNAI TERHADAP PERUBAHAN RETURN SAHAM - Chadilla, Ainul (Manajemen Bisnis, 2014)
This research aims to analyze the effect of cash devidend payment announcement on stock return. Compass 100 Index is a collection of 100 companies that have good financial performance as well as changes in the level and frequency of transactions is high prices. The result showed that there was a significant effect between cash devidend payment announcement and stock return changes. Some conditions showed an abnormal return, where in period t-2, t0, t1 and t3 were greater than t tables. It indicates that the payment announcement of cash devidend information increasing market trust and investor attractive.Keywords: Cash Dividend Payment Announcement, Stock Return changes, Compass 100 Index